2011
DOI: 10.2478/v10051-011-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Baselines for the Preparation of Electronic Textbooks

Abstract: Baselines for the Preparation of Electronic Textbooks The NAUK group (Advanced Learning Blocks group; http://www.nauk.si) is engaged in the development of theoretical and practical concepts of ICT use in all levels of education. Recently, the proposed introduction of electronic textbooks (e-textbooks) has become a major topic nationwide in Slovenia. There are multiple dilemmas to be solved, e.g. what a modern e-textbook is, what it should include, in what way should it differ from conventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Defining what an e-textbook is can be unclear. An e-textbook can be a digital copy of a traditional text in a PDF file or can be the text embedded in an interactive platform with advanced features (Chesser, 2011; Lokar et al , 2011). Some e-textbook formats allow teachers to modify information and add instructional tools for students to use while reading (Hull and Lennie, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining what an e-textbook is can be unclear. An e-textbook can be a digital copy of a traditional text in a PDF file or can be the text embedded in an interactive platform with advanced features (Chesser, 2011; Lokar et al , 2011). Some e-textbook formats allow teachers to modify information and add instructional tools for students to use while reading (Hull and Lennie, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers can change how they present information when using e-textbooks. Therefore, they might have to take the time to learn various methods for doing this before they adopt these techniques in the classroom (Acker, 2011; Lokar et al , 2011). This is imperative since Johnston et al (2015) found that students tend to not take advantage of the unique features found in e-textbooks unless the teacher models how to use e-book features.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, often these involve improving the readability of the text rather than improving the teaching value (Gunawan, 2018). Others have focused on factors such as interoperability of content across platforms and lifespan of software tools used to create e-books and e-textbooks (Lokar et al, 2011). A third group has focused on the types of information that e-textbooks should contain (Ivanova and Osmolovskaya, 2016).…”
Section: Introductionmentioning
confidence: 99%